2017
DOI: 10.1073/pnas.1707713114
|View full text |Cite
|
Sign up to set email alerts
|

Network of nutrient-sensing pathways and a conserved kinase cascade integrate osmolarity and carbon sensing in Neurospora crassa

Abstract: Identifying nutrients available in the environment and utilizing them in the most efficient manner is a challenge common to all organisms. The model filamentous fungus Neurospora crassa is capable of utilizing a variety of carbohydrates, from simple sugars to the complex carbohydrates found in plant cell walls. The zinc binuclear cluster transcription factor CLR-1 is necessary for utilization of cellulose, a major, recalcitrant component of the plant cell wall; however, expression of clr-1 in the absence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 57 publications
(95 reference statements)
1
69
2
Order By: Relevance
“…Although not a transcription factor, CLR-3 (NCU05846) is still highly relevant for cellulase regulation (Huberman et al, 2017) and was found to be phosphorylated in two regions and three potential sites (Supplementary Material 2). Interestingly, phosphorylation of T713 within a predicted casein kinase II phosphorylation site was specific for the absence of carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not a transcription factor, CLR-3 (NCU05846) is still highly relevant for cellulase regulation (Huberman et al, 2017) and was found to be phosphorylated in two regions and three potential sites (Supplementary Material 2). Interestingly, phosphorylation of T713 within a predicted casein kinase II phosphorylation site was specific for the absence of carbon.…”
Section: Resultsmentioning
confidence: 99%
“…The Mitogen-Activated Protein Kinase (MAP kinase) pathway, for example, represents a prototype of a signal distribution channel with phosphorylation being the major switch. In N. crassa, MAP kinases are known to be involved in cell-to-cell communication (Fischer et al, 2018), circadian regulation of cellular processes (Bennett et al, 2013; Lamb et al, 2012), phosphate signaling (Gras et al, 2013) as well as sensing of osmolarity and carbon (Huberman et al, 2017). Phosphorylation/dephosphorylation reactions involved in nutrient-sensing are furthermore central to the cyclic AMP (cAMP) signal transduction pathway (Aichinger et al, 1999; Ficarro et al, 2002; Lengeler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Clr-1 is another transcription factor that is necessary for cellulose utilization. However, its regulation of cellulase gene expression is strongly influenced by inducers: Clr-1 cannot induce the expression of the cellulase gene without an inducer [102]. In the presence of an inducer, such as cellobiose, a degradation product of cellulose, Clr-1 induces the expression of some genes containing β-glucosidases and Clr-2, a transcription regulator [103].…”
Section: Molecular Regulation Mechanisms Of Cellulase Gene Expressionmentioning
confidence: 99%
“…Through the screening of mutants in the absence of an inducer, a Clr-3 that inhibits the activity of Clr-1 was identified in N. crassa. It was found that the deletion of the clr-3 gene led to cellulase gene expression of Clr-1-dependent even without an inducer [102,105].…”
Section: Molecular Regulation Mechanisms Of Cellulase Gene Expressionmentioning
confidence: 99%
“…Huberman et al . () recently identified a new repressor, CLR‐3, that acts through CLR‐1 to repress the cellulolytic response. Their results also showed that the hyperosmotic response pathway regulates the transcription of cellulase genes in N. crassa (Huberman et al ., ).…”
Section: Introductionmentioning
confidence: 99%